Evolutionarily divergent thermal sensitivity of germline development and fertility in hermaphroditic Caenorhabditis nematodes. Issue 6 (23rd October 2015) - Poullet, Nausicaa; Vielle, Anne; Gimond, Clotilde; Ferrari, Céline; Braendle, Christian
SUMMARY Thermal developmental plasticity represents a key organismal adaptation to maintain reproductive capacity in contrasting and fluctuating temperature niches. Although extensively studied, research on thermal plasticity has mainly focused on phenotypic outcomes, such as adult life history, rather than directly measuring plasticity of underlying developmental processes. How thermal plasticity of developmental phenotypes maps into plasticity of resulting final phenotypes, and how such mapping relationships evolve, thus remain poorly understood. Here we address these questions by quantifying thermal plasticity of Caenorhabditis hermaphrodite germline development. We integrate measurements of germline development and fertility at the upper thermal range in isolates of C. briggsae, C. elegans, and C. tropicalis. First, we compare intra‐ and interspecific variation in thermal germline plasticity with plasticity in reproductive output. Second, we ask whether the developmental errors leading to fertility break‐down at upper thermal limits are evolutionarily conserved. We find that temperature variation modulates spermatogenesis, oogenesis and germ cell progenitor pools, yet the thermal sensitivity of these processes varies among isolates and species, consistent with evolutionary variation in upper thermal limits of hermaphrodite fertility. Although defective sperm function is a major contributor to heat‐induced fertility break‐down, high temperature also significantly perturbs oogenesis, germline integrity, and mitosis–meiosis progression. Remarkably, the occurrence and frequency of specific errors are strongly species‐ and genotype‐dependent, indicative of evolutionary divergence in thermal sensitivity of distinct processes in germline development. Therefore, the Caenorhabditis reproductive system displays complex genotype‐by‐temperature interactions at the developmental level, which may remain masked when studying thermal plasticity exclusively at the life history level.